Seismic Strength Assessment of An Oil Product Storage Tank Under Full Product Filling Conditions (Texas Journal of Engineering and Technology, 2026)
This study presents technical solutions aimed at reducing the seismic vulnerability of existing storage tanks. Scientific and engineering proposals are developed to enhance the seismic resistance of the tank, and structural strengthening measures are formulated based on numerical analyses performed using the LIRA-SOFT 10.12 software package. Based on the obtained results, effective engineering solutions are proposed to mitigate seismic impacts and improve the overall structural safety and reliability of the tank.(This article was prepared within the framework of the project of the Ministry of Higher Education, Science and Innovation of the Republic of Uzbekistan on the topic of determining the level of seismic resistance of reservoirs in the oil and oil and gas industry and developing measures to reduce seismic risk, scheduled for implementation in 2024-2025)